2021
DOI: 10.1007/s12369-021-00797-3
|View full text |Cite
|
Sign up to set email alerts
|

Sexbots as Synthetic Companions: Comparing Attitudes of Official Sex Offenders and Non-Offenders

Abstract: This is the first Italian study to examine views on sexbots of adult male sex offenders and non-offenders, and their perceptions of sexbots as sexual partners, and sexbots as a means to prevent sexual violence. In order to explore these aspects 344 adult males were involved in the study. The study carried out two types of comparisons. 100 male sex offenders were compared with 244 male non-offenders. Also, sex offenders were divided into child molesters and rapists. Preliminary findings suggest that sex offende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 108 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…Child-like sex dolls and sex robots are considered particularly dangerous, and their production and possession is already criminalized in some countries ( Maras and Shapiro, 2017 ; Brown and Shelling, 2019 ). The idea that female or child-like sex dolls and sex robots could successfully be used in the therapy of sex offenders is met with skepticism by ethicists, therapists, and sex offenders ( Zara et al, 2021 ).…”
Section: Sexual Interaction With Digital Technologiesmentioning
confidence: 99%
“…Child-like sex dolls and sex robots are considered particularly dangerous, and their production and possession is already criminalized in some countries ( Maras and Shapiro, 2017 ; Brown and Shelling, 2019 ). The idea that female or child-like sex dolls and sex robots could successfully be used in the therapy of sex offenders is met with skepticism by ethicists, therapists, and sex offenders ( Zara et al, 2021 ).…”
Section: Sexual Interaction With Digital Technologiesmentioning
confidence: 99%
“…Sex robots as a solution to this makes no sense (viz. Sparrow, 2017;Zara et al, 2021), both given the complex socioeconomic reasons for human trafficking and the fact that non-coercive and ethical sex work exists, and has existed from antiquity long before the modern illegal industry of human trafficking, meaning that it is not caused (in a simple or straightforward way) by lack of access to buying sex.…”
Section: Cheyenne Macdonald 2019mentioning
confidence: 99%
“…It's only a thing, and it might even do some good. For instance, it has been suggested that sex robots, used within controlled environments, could help redirect "the sexual behavior of high-risk child molesters … without endangering real children" (Zara et al 2022). The two routes to discussing the ethical issues of sex robots sketched above could also be illustrated as a continuum with two opposing poles which meet where sexual autonomy that does not create harm might be the Aristotelian golden mean (Aristotle 2000(Aristotle : 102 [1138b).…”
Section: Universal Declaration Of Human Rights Article 25mentioning
confidence: 99%